2016
DOI: 10.1155/2016/9869712
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Review of Psychological Stress in Parkinson’s Disease: Biological Mechanisms and Symptom and Health Outcomes

Abstract: Parkinson's disease (PD) is characterized by complex symptoms and medication-induced motor complications that fluctuate in onset, severity, responsiveness to treatment, and disability. The unpredictable and debilitating nature of PD and the inability to halt or slow disease progression may result in psychological stress. Psychological stress may exacerbate biological mechanisms believed to contribute to neuronal loss in PD and lead to poorer symptom and health outcomes. The purpose of this integrated review is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…In our conceptual framework, a stressor is considered as any perceived or actual threat to an individual that has the capacity to disrupt homeostasis and cause stress [59]. Most people experience acute stress in response to a stressful event over the life course; however, chronic stress may be more problematic since it can increase one’s risk for several health problems like heart disease [60], neurologic and psychiatric diseases [61], Parkinson’s disease [62], Alzheimer’s disease [63], multiple sclerosis [64], eating disorders [65], addictions [66], post-traumatic stress disorder (PTSD) [67], and sleeping complications [68].…”
Section: Resiliency-stressor Conceptual Framework Componentsmentioning
confidence: 99%
“…In our conceptual framework, a stressor is considered as any perceived or actual threat to an individual that has the capacity to disrupt homeostasis and cause stress [59]. Most people experience acute stress in response to a stressful event over the life course; however, chronic stress may be more problematic since it can increase one’s risk for several health problems like heart disease [60], neurologic and psychiatric diseases [61], Parkinson’s disease [62], Alzheimer’s disease [63], multiple sclerosis [64], eating disorders [65], addictions [66], post-traumatic stress disorder (PTSD) [67], and sleeping complications [68].…”
Section: Resiliency-stressor Conceptual Framework Componentsmentioning
confidence: 99%
“…The relationship between psychological stress and onset of neurodegenerative disease is not an unexplored one. For example, links between stress and Parkinson disease (PD) have been proposed ( Djamshidian and Lees, 2014 ; Austin et al, 2016 ), and refuted ( Clark et al, 2013 ). However, a prospective study that examined vagal tone indicated by vagally mediated HRV in relation to risk of PD showed that low vagal tone was associated with higher risk of PD 18 years later ( Alonso et al, 2015 ).…”
Section: Applying the Model: Neurodegenerative Disease And Cancermentioning
confidence: 99%
“…Glucocorticoids play an important role in regulating microglial activation and proinflammatory cytokine transcription factor expression and release . Dysregulation of this system has been found to cause neuroinflammation, oxidative stress, and loss of dopamine‐producing neurons within the CNS . Although little is known with respect to the effect of chronic stress on PD‐associated constipation, stress is known to contribute to the onset and/or severity of GI dysfunction in the general population …”
Section: Introductionmentioning
confidence: 99%